Sources and levels of selenium on breast meat quality of broilers - Boiago, Marcel Manente; Borba, Hirasilva [UNESP]; Leonel, Fábio Roberto; Giampietro-Ganeco, Aline [UNESP]; Ferrari, Fábio Borba [UNESP]; Stefani, Lenita Moura; Souza, Pedro Alves de [UNESP] (Universidade Federal de Santa Maria, 2014)
Qualitative characteristics of breast meat of broilers fed diets supplemented with different concentrations (0; 0.3 and 0.5mg kg-1) of selenium in the form of selenomethionine and sodium selenite were analyzed. A total of 1050 one-day-old male Cobb broiler chicks were arranged factorially at random to five treatments (two concentrations x two sources + control diet without addition of selenium) with 7 replications of thirty birds each and received an isonitrogenous and isocaloric diets in all phases according to their ages (1-21, 22-35, and 36-42 days). At 42 days of age, TBARS (thiobarbituric acid reactive substances) after storage at 4ºC for one, seven and 15 days and also after 30 days under freezing temperatures (-15°C), color (CIELab), water holding capacity, cooking loss, shear force, pH and selenium concentration were determined in slaughtered birds breast meat. Results indicated that the use of selenomethionine provides less lightness and lower oxidation in chicken breast meat stored up to 15 days at 4°C. There was a positive effect of dietary different sources and levels of selenium on breast meat quality of broilers. It was observed a linear effect of dietary selenium levels on the amount of selenium deposited in the muscle, and the organic source (selenomethionine) is more effective than inorganic one (sodium selenite) for broiler meat conservation.

Analisaram-se características qualitativas da carne do peito de frangos de corte alimentados com rações suplementadas com diferentes concentrações (0; 0,3 e 0,5mg kg-1) de selênio nas formas de selenometionina e selenito de sódio. Foram utilizados 1050 pintainhos machos de um dia de idade da linhagem Cobb, que foram distribuídos em delineamento inteiramente casualizado em esquema fatorial em 5 tratamentos (duas concentrações x duas fontes + tratamento controle, sem adição de selênio) e sete repetições de trinta aves cada e receberam rações isoproteicas e isoenergéticas em todas as fases de criação (1 a 21, 22 a 35 e 36 a 42 dias). Aos 42 dias de idade, TBARS (substâncias reativas ao ácido tiobarbitúrico) após armazenamento a 4ºC por um, sete e 15 dias e 30 dias sob congelamento (15ºC), coloração (CIELab), capacidade de retenção de água, perdas de peso por cocção, força de cisalhamento, pH e concentração de selênio foram determinadas na carne do peito das aves abatidas. Os resultados indicaram que o uso da selenometionina ocasiona queda da oxidação da carne e luminosidade aos 15 dias de armazenamento a 4ºC. Existiu um efeito positivo da suplementação da ração com as diferentes fontes e concentrações de selênio sobre a qualidade da carne do peito das aves. Houve efeito linear dos níveis dietéticos de selênio na quantidade de selênio depositado no músculo, e a fonte orgânica (selenometionina) foi mais efetiva que a inorgânica (selenito de sódio) na conservação da carne de frango.
Fontes e níveis de selênio sobre a qualidade da carne do peito de frangos de corte
Keywords: frango de corte; qualidade da carne; pectoralis major; selenito de sódio; selenometionina; broiler; meat quality; pectoralis major; selenomethionine; sodium selenite